Cross-border insolvency of enterprise groups: the choice of law challenge - Mevorach, Irit (Brooklyn Law School, 2014)
It is not surprising that the problems of choice of law and international group insolvency have not been sufficiently addressed during the initial development of cross-border insolvency frameworks. The choice of law problem raises difficult questions and affects substantive rights in the context of cross-border insolvency. International group enterprises come about in different legal and operational structures, requiring a sufficiently nuanced regime that could properly accommodate the diverse types of groups. Generally, the regulation of groups is difficult, as it raises a concern of defeating the economic merits of the corporate form. Addressing the combined problem of international groups and choice of law presents significant challenges, and requires careful analysis of economic structures and their implications on both creditors’ expectations regarding their substantive rights and the ability to achieve efficient solutions in insolvency. This Article aims to provide a roadmap of choice of law solutions in international enterprise group cases, and to compare these solutions with the existing cross-border insolvency practice and the cross-border insolvency frameworks.